2016
DOI: 10.1177/1044207315604366
|View full text |Cite
|
Sign up to set email alerts
|

Professional Practice and Ethical Issues Related to Physical Restraint and Seclusion in Schools

Abstract: Use of physical restraint and seclusion procedures in schools continues to be controversial, and foster proposals for federal and state legislation and regulation. Despite much discussion about what policies are needed, there has been little discussion about the professional practice issues and the ethical issues related to these practices. The purpose of this report is to present six clusters of professional practice and ethical issues that have not heretofore been specifically identified. To do so, we will e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 20 publications
1
26
0
1
Order By: Relevance
“…Several factors such as appropriateness of ethical teaching, trained ethical content, personal characteristics, and so on can influence professional ethics development in health sciences students. 12,13 Studies in Iran indicate that health sciences students suffered from ethical stress when making ethical decisions in clinical settings. 14 It seems that part of this incompetence is reflected in the educational system and lack of appropriate development of professional ethics in students during the study.…”
Section: Introductionmentioning
confidence: 99%
“…Several factors such as appropriateness of ethical teaching, trained ethical content, personal characteristics, and so on can influence professional ethics development in health sciences students. 12,13 Studies in Iran indicate that health sciences students suffered from ethical stress when making ethical decisions in clinical settings. 14 It seems that part of this incompetence is reflected in the educational system and lack of appropriate development of professional ethics in students during the study.…”
Section: Introductionmentioning
confidence: 99%
“…Policy guidance from the U.S. Department of Education states that “incidents of child misbehavior and classroom disruptions, as well as violations of a code of student conduct, may indicate that the child’s IEP needs to include appropriate behavioral supports” (Swenson & Ryder, 2016); however, this review indicates that seclusion and restraint for students with disabilities are topics of great importance, but little planning or appropriate action is taken. Scheuermann, Peterson, Ryan, and Billingsley (2015) found six clusters of ethical issues related to seclusion and restraint:(a) potential for death or injury; (b) failure to use the least intrusive intervention; (c) inappropriate restrictions on liberty and removal from access to education; (d) repeated use of a potentially dangerous and ineffective intervention; (e) disproportionate use with certain groups; and (f) insufficient professional training, supervision, and monitoring. (p. 3)…”
Section: Discussionmentioning
confidence: 99%
“…GAO, 2009). The improper use of these procedures has resulted in reports of students harming themselves, or suffering severe injuries or death (Masters et al, 2002; Scheuermann et al, 2016). Most of the vendors reported that they routinely allot time to discuss seclusion procedures and risks during training.…”
Section: Discussionmentioning
confidence: 99%
“…The use of seclusion and restraint procedures in schools continues to garner negative attention across the United States, especially in light of the numerous allegations of misuse and abuse with students. Scheuermann and colleagues (2016) identified a half dozen professional and/or ethical issues related to the use of seclusion and/or restraint. Three major categories of ethical issues identified were insufficient or inadequate training, supervision, and monitoring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation